2017
DOI: 10.31237/osf.io/943hr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Water stress detection using radar

Abstract: NOMENCLATUREV 2 Water-cloud vegetation model parameter [-]

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 172 publications
(344 reference statements)
0
4
0
Order By: Relevance
“…In dense forest canopies, therefore, the backscatter from such microwaves easily saturates and represents only a cross-section of the top canopy. However, the edge of forests or canopy trees is particularly significant for radar system as such edges can provide conditions that result in "double-bounce" backscatter [69,78]. The co-polarized backscatter is sensitive to conditions of double bounce which is provided by surface components of vegetation [69].…”
Section: Sensitivity Of S-1a Backscatter (Vv Vs Vh) To Canopy Gap Fra...mentioning
confidence: 99%
“…In dense forest canopies, therefore, the backscatter from such microwaves easily saturates and represents only a cross-section of the top canopy. However, the edge of forests or canopy trees is particularly significant for radar system as such edges can provide conditions that result in "double-bounce" backscatter [69,78]. The co-polarized backscatter is sensitive to conditions of double bounce which is provided by surface components of vegetation [69].…”
Section: Sensitivity Of S-1a Backscatter (Vv Vs Vh) To Canopy Gap Fra...mentioning
confidence: 99%
“…All data were collected around the K34 observatory (130 m above Mean Sea Level) in the Amazon rainforest (2.6085 • S, 60.2093 • W), 60km Northwest of Manaus, Brazil (see van Emmerik et al, 2017). A map of the measurement location, including the measured trees and the K34 observatory is presented in Figure 1A.…”
Section: Measurement Locationmentioning
confidence: 99%
“…More recently, Jackson et al (in review) demonstrated that there is a significant difference between trees during summer (with leaves) and winter (no leaves). van Emmerik (2017) and van Emmerik et al (2018a) related changes in tree sway to water stress induced mass changes, which was hypothesized to be caused by decreasing tree water content and/or leaf fall. Future efforts might focus on using tree sway data to quantify tree mass changes on even lower time scales.…”
Section: Tree Mass Variationsmentioning
confidence: 99%
See 1 more Smart Citation